Change Your Ways: Fostering Health Attitudes Toward Change Through Selective Exposure to Online Health Messages - Westerwick, Axel; Johnson, Benjamin K.; Knobloch-Westerwick, Silvia (Health communication, 2017)
Health information is often sought online, despite varying credibility of online sources, and may shape health behaviors. This investigation builds on the Selective Exposure Self- and Affect-Management model to examine selective exposure to online health information from low- and high-credibility sources and subsequent effects on attitudes toward health behaviors. In a lab study, 419 participants accessed online search results about health topics. The display varied messages in a 4 × 2 × 2 all within-subjects design, with topic as a four-step factor (organic food, coffee, fruit and vegetable consumption, physical exercise) and source credibility (low vs. high) and issue stance (promoting vs. opposing health behavior) as two-step factors. Displayed messages either promoted or opposed the related behavior. Results showed that perceiving greater standard-behavior discrepancy (between recommended behavior standards and own behavior) fostered behavior-related attitudes through selective exposure to messages promoting that behavior. The effects from selective exposure to health messages on attitudes occurred regardless of associated source credibility.